Konsep Syukur Dan Kecerdasan Emosional Perspektif Imam Al – Ghazali Dalam Kitab Ihya Ulumuddin - Rayhanil Jannah; Wijaya; Erika Septiana (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Gratitude is an attitude that must exist in humans because gratitude is a way of expressing gratitude for the blessings that have been given by Allah. This study aims to determine the concept of gratitude in Kitab Ihya Ulumuddin Karangan Al-Ghazali along with aspects of emotional intelligence that are relevant to the concept of gratitude from Al-Ghazali's perspective in Kitab Ihya Ulumuddin. The type of research used in this is qualitative, data collection techniques using library research (library reserch) relying on literature. This research uses descriptive analysis techniques. The results of the research on the concept of gratitude are realized in several characteristics, namely knowledge, things, and deeds of emotional intelligence aspects that are relevant to gratitude in the Book of Ihya Ulumuddin.